Estudos sobre acesso aos serviços de saúde bucal no Brasi. - TEIXEIRA, Cinthia Nara Gadelha (2020)
Access to oral health services in Brazil is exclusive, being determined by numerous factors that guide the lives of individuals. Measuring what these factors are and evaluating how access to oral health services in Brazil takes place, from the perspective of vulnerable populations, is still a gap in the literature. This thesis aimed to evaluate the variables associated with the frequency of use of oral health services in Brazil (Chapter I) and access to primary health care (PHC) oral health services and associated variables, by quilombolas in Maranhão, Brazil (Chapter II). Chapter I was a systematic review study with meta-analysis, including the PubMed, SciELO, LILACS, BBO, EMBASE, Scopus, WOS and Google Scholar databases, as well as reference lists and sites for dissertations and theses. Observational studies were selected using the PEO (Population/Exposure/Outcome) strategy in May 2020. The outcome of this study was the frequency of use of oral health services in the last year. A Mantel-Haenszel random effect meta-analysis was performed, using the Prevalence Ratio (PR) and 95% confidence interval as measures of association. In Chapter II, a cross-sectional population-based study was carried out in the Santa Rosa dos Pretos quilombo, in Itapecuru Mirim, in the state of Maranhão. Adult users who had lived in the household for at least 12 months were included, and individuals who had been absent from the household for 6 or more months were excluded, as well as those who did not have health conditions to answer the questionnaires. Data were collected by previously trained researchers through structured questionnaires. Questionnaires captured sociodemographic information; socioeconomic; from self-perception to oral health; discrimination; in addition to the oral health assessment in PHC, through the Primary Care Assessment Tool – Oral Health of Adults (PCATool-OH). Three attributes of PCATool-OH were used: affiliation; first-contact access-use; first-contact access-accessibility; in addition to the access score. A cutoff point >5.5 was used for high scores on access to oral health services in the PHC. The association between the mean scores in relation to the independent variables was assessed using the Mann-Whitney or Kruskal-Wallis tests. In the multivariate analysis, Poisson Regression was used. Analyzes were performed adopting a 95% confidence level and a 5% significance level. In chapter I, 94 studies were selected, 25 of which were aggregated in the meta-analysis. The use of oral health services in the last year was associated with higher education (PR=0.49, (95%CI:0.39-0.60)); higher family income (PR=0.79, (95%CI:0.74-0.84)); and urbanity (RP=0.79, (95%CI:0.64-0.97)). In chapter II, 293 individuals participated in the study, with mean and standard deviation of the access score of 3.93 (SD ± 1.37), where 91.4% classified the access score as poor. There was an association between self-perception of oral health with the attributes affiliation (p=0.049), first contact access (use) (p=0.014), and with the access score (p=0.002). An association was also observed between monthly family income and the attribute of first contact access (accessibility) (p=0.012). In chapter I, it was possible to conclude that the frequency of use of oral health services in Brazil is uneven, reinforcing the need for public policies and programs that promote access and use by more vulnerable groups. In chapter II, it was possible to conclude that the assessment of access to PHC oral health services by the quilombolas of Santa Rosa dos Pretos was poor, requiring the strengthening of this service, focusing on vulnerable populations.